Pengaruh Literasi Keuangan dan Modal Minimum Investasi Terhadap Minat Investasi Cash Waqf Linked Sukuk Pada Generasi Z - Fadhil Rakhmad; Lisa Martiah Nila Puspita (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to determine how the level of financial literacy and minimum investment capital affects the interest in investing in Cash Waqf Linked Sukuk. The population for this analysis is the Gen Z community in Indonesia, and the sample was taken in June 2024. Smart-PLS software is used to perform multiple linear regression analysis. The technique used in sampling is non probability sampling and uses purposive sampling method consisting of 343 respondents The test results of Partial Least Square (PLS) Structural Model Method show that both variables (financial literacy and minimum capital) have a positive influence on investment interest in Cash Waqf Linked Sukuk with P values of 0.000 for the level of financial literacy and P values of 0.000 for minimum investment capital. This explains that the higher the level of financial literacy of generation z and the lower the minimum investment capital for generation z, the higher the interest of generation z to invest in Cash Waqf Linked Sukuk.